2015
DOI: 10.1371/journal.pone.0124287
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cardiovascular Outcomes after Dipeptidyl Peptidase-4 Inhibitor, Sulfonylurea, and Pioglitazone Therapy, All in Combination with Metformin, for Type 2 Diabetes: A Population-Based Cohort Study

Abstract: Background/ObjectivesData on the comparative effectiveness of oral antidiabetics on cardiovascular outcomes in a clinical practice setting are limited. This study sought to determine whether a differential risk of cardiovascular disease (CVD) exists for the combination of a dipeptidyl peptidase-4 (DPP-4) inhibitor plus metformin versus a sulfonylurea derivative plus metformin or pioglitazone plus metformin.MethodsWe conducted a cohort study of 349,476 patients who received treatment with a DPP-4 inhibitor, sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 36 publications
8
57
0
1
Order By: Relevance
“…Effects on hospital admission for heart failure All five trials 9 evidence from observational studies Of 12 observational studies, four [109][110][111][112] reported heart failure, and eight 13-17 113-115 reported hospital admission for heart failure; nine 13-15 109-111 [113][114][115] were cohort studies and the other three 16 17 112 were nested case-control studies (fig 1). Observational studies reporting heart failure Of the four studies reporting heart failure, two prospective cohort studies 109 (table 4 and table 5).…”
Section: Trials Reporting Hospital Admission For Heart Failurementioning
confidence: 99%
“…Effects on hospital admission for heart failure All five trials 9 evidence from observational studies Of 12 observational studies, four [109][110][111][112] reported heart failure, and eight 13-17 113-115 reported hospital admission for heart failure; nine 13-15 109-111 [113][114][115] were cohort studies and the other three 16 17 112 were nested case-control studies (fig 1). Observational studies reporting heart failure Of the four studies reporting heart failure, two prospective cohort studies 109 (table 4 and table 5).…”
Section: Trials Reporting Hospital Admission For Heart Failurementioning
confidence: 99%
“…Furthermore, the comparability with the study of Gallwitz et al is limited since linagliptin is not sold in Germany and it is unclear whether the results for linagliptin hold true for all DPP-4 inhibitors. The only study that included heart failure as part of the cardiovascular event was the one conducted by Seong et al (2015) based on Korean health insurance data. The authors reported a significantly increased risk of 20% for a cardiovascular event in patients with a combination therapy of metformin and sulfonylureas compared to DPP-4 inhibitors, which is similar to the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, occurrence of heart failure was not investigated in these studies. A recently conducted observational study based on data of Korean national health insurances observed an increased risk of total cardiovascular disease but not of heart failure for a combination of metformin and sulfonylureas compared to metformin and DPP-4 inhibitors (Seong et al, 2015).…”
mentioning
confidence: 99%
“…Dans ces études, la pioglitazone s'est révélée être associée à un meilleur pronostic CV (hormis le risque d'insuffisance cardiaque qui était accru) que la metformine [18] ou qu'un sulfamide hypoglycémiant chez des patients par ailleurs déjà traités par metformine [31]. De plus, quelques études observationnelles ont comparé le devenir de patients DT2 traités par glitazones, et ont montré que la pioglitazone était associée à un meilleur pronostic que la rosiglitazone [18,32].…”
Section: éTudes Observationnelles De Cohorteunclassified